Structural and Mechanistic Studies of Mofegiline Inhibition of Recombinant Human Monoamine Oxidase B - Milczek, Erika M. (2008)
Mechanistic and structural studies have been carried out to investigate the molecular basis for the irreversible inhibition of human MAO-B by mofegiline. Competitive inhibition with substrate shows an apparent K(i) of 28 nM. Irreversible inhibition of MAO-B occurs with a 1:1 molar stoichiometry with no observable catalytic turnover. The absorption spectral properties of mofegiline inhibited MAO-B show features (λ(max) ≃ 450 nm) unlike those of traditional flavin N(5) or C(4a) adducts. Visible and near UV circular dichroism spectra of the mofegiline-MAO-B adduct shows a negative peak at 340 nm with an intensity similar to that of N(5) flavocyanine adducts. The x-ray crystal structure of the mofegiline-MAO-B adduct shows a covalent bond between the flavin cofactor N(5) with the distal allylamine carbon atom as well as the absence of the fluorine atom. A mechanism to explain these structural and spectral data is proposed.